Cover Feature: Rational Development of Neutral Aqueous Electrolytes for Zinc–Air Batteries (ChemSusChem 23/2017). Issue 23 (4th December 2017) - Clark, Simon; Latz, Arnulf; Horstmann, Birger
Abstract : The Cover Feature shows a schematic of a promising zinc–air battery with a water‐based, pH‐neutral electrolyte. Zinc–air batteries are safe, use common and non‐toxic materials, and could achieve a significant increase in energy density over lithium‐ion batteries. Successful development of this battery could have far‐reaching implications for renewable energy storage and electric mobility. This study presents the first continuum simulation of zinc–air batteries in aqueous ZnCl2 –NH4 Cl, and derives a new framework for modeling pH‐buffered electrolytes. More information can be found in the Full Paper by Clark et al. onpage 4735 in Issue 23, 2017 (DOI:10.1002/cssc.201701468 ).